Pembuatan Game Visual Novel “One Year Of Time” pada Platform Website - Jonathan Suryadi; Darius Andana Haris; Jeanny Pragantha (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The game “One Year of Time” is a form of interactive entertainment that engages players in rule-based activities with specific goals. Besides recreation, games also help develop critical thinking, problem-solving, strategic planning, and hand-eye coordination skills. “One Year of Time” is a 2D romance visual novel developed using Unity and programmed in C# for the web platform. Players take on the role of a god named Aion, who is descended to the human world due to a violation of the laws imposed by Zeus and is punished with a one-year time limit to find a partner—or face extinction. Along the way, players meet three main female characters, each with a unique personality. Each choice they make affects their relationships and determines the outcome of the story. Through these decisions and challenges, players explore the meaning of love, human relationships, and the consequences of their actions. Testing of this game was conducted. The game was tested using three methods: black box testing, an alpha test conducted by a supervisor, and a beta test conducted by 33 participants. The test results indicated that "One Year of Time" was considered engaging, easy to understand, and potentially well-received by players. This demonstrates the game's entertainment value and replayability. Therefore, it can be concluded that the game successfully provided a positive gaming experience and has potential for further development.